Willa the wisp - Auxier, Jonathan; Demidova, Olga (New York : Amulet Books, 2020)
One day eight-year-old Auggie Pound, the caretaker of the rare animals in the Fabled Stables, ventures into the swamp to save a new rare creature, the wisp.
K-3
P
2.8
Keywords: Imaginary creatures -- Fiction; Animals, Mythical -- Fiction; Friendship -- Fiction; Fantasy fiction